Continental subduction of Adria in the Apennines and relation with seismicity and hazard - Chiarabba, C.; Menichelli, I.; Bianchi, I.; Giacomuzzi, G.; De Gori, P. (Frontiers in Earth Science, 2023)
The subduction of continental lithosphere is a complex process because the buoyancy of the crust is higher than the oceanic and should resist sinking into the mantle. Anyway, studies on the Alpine-Himalayan collision system indicate that a large portion of the continental crust is subducted, while some material is accreted in the orogens. The Apennine is a perfect case for studying how such processes evolve, thanks to high quality seismic images that illuminate a critical depth range not commonly resolved in many collisional settings. In this paper, we show the structure of the Apennines orogen, as jointly revealed by seismicity and deep structure from regional and teleseismic tomography and receiver function profiles. The westward subducting Adria lithosphere is well defined along the orogen showing a mid-crustal delamination. Seismicity within the underthrusting lower crust and velocity anomalies in the mantle wedge highlight how the subduction evolution is entangled with the liberation of fluids. The eclogitization of subducted material enhances the fluid release into the wedge, the delamination and retreat of the Adria plate. This delamination/subduction generates a coupled compression and extension system that migrates eastward following the retreat of the lithosphere, with broad sets of normal faults that invert or interfere with pre-existing compressional structures all over the roof plate. The sparseness and non-ubiquity of intermediate depth earthquakes along the subduction panel suggest that the brittle response of the subducting crust is governed by its different composition